Some biological and genomic properties of pigeonpea isolate of mungbean yellow mosaic geminivirus - and V.G. MALATHI, BIKASH MANDAL, ANUPAM VARMA (Indian Phytopathology, 2002)
The causal virus of yellow mosaic of pigeon pea (Cajanus cajan) was found to be an extended host range phenotype of mungbean yellow mosaic geminivirus (MYMV). The pigeonpea isolate (MYMV-Pp) could be transmitted by whitefly (Bemisia tabaci) to mungbean (Vigna radiata), blackgram (Vigna mungo), Frenchbean (Phaseolus vulgaris), soybean (Glycine max), Iimabean (Phaseolus lunatus), horsegram (Macrotyloma unijlorum) and cowpea (Vigna unguiculata). Double stranded DNA forms (open circular, linear and supercoiled) from infected plants were purified and cloned in to pUC18 and pBluescript SK+ vectors; four full length clones were obtained. All the four clones obtained were found to be D A-B on the basis of hybridization with MYMV-Bg DNA-B. Restriction analysis of clone pMY-PB3 revealed that it had a pattern similar to that of MYMV-Bg (blackgram isolate) D A-B, suggesting that MYMV-Bg and MYMV-Ppl are closely related. D A-B of MYMV-Ppl, however, differed considerably in its restriction maps from that of MYMV-T, a mechanically transmissible isolate characterised from Thailand. D A-B probes detected MYMV-Ppl in the plants, and in adults and pupae of viruliferous whiteflies.